Current account sustainability in the US: What do we really know about its? - Dimitris K. Christopoulos; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2004)
We revisit the debate on the sustainability of the current account dynamics in the US. Using the concept of sustainability as the ability to meet the long run intertemporal budget constraint, we test for unit roots in the US current account for the 1960-2004 period. We argue that there are several reasons to believe that the current account may follow a non-linear behaviour under the null of stationarity. This is confirmed by a set of non-linearity tests. We then fit an ESTAR model to the current account dynamics and reject the null of non-stationarity. Hence, we conclude in favour of sustainability. Furthermore, our results reveal that only for the period 1974-1992 we can find significant deviations of the current account from equilibrium and a slower speed of mean reversion.
Keywords: C22; F32; 330; Current account sustainability; stationarity; non-linear models; Leistungsbilanz; Volatilität; Unit Root Test; Schätzung; USA; Nichtlineares Verfahren